State Sukuk Potential in Reducing Indonesia Budget Deficit, 2009-2015 - Ima Amaliah; Tasya Aspiranti (Universitas Hayam Wuruk Perbanas, 2017)
The purpose of this study is to identify potential retail state sukuk as part of state bonds that are used to replace foreign debt and lower the government's budget deficit. This study is important because the government's budget deficit continues to rise each year due to the increase of foreign debt. The increase in the debt itself is closely related to exchange rate fluctuations. Therefore, it is important for the government to develop a relatively secure funding in facing exchange rate fluctuations as well as parts of interest rate. The government has developed state securities based on sharia (SBSN) which can be used not only to close finance deficit but also to alternatively finance the infrastructure development. The population consists of budget deficit, retail state sukuk, corporate sukuk, and foreign debt. It uses purposive sampling to get the sample during 2009 -2015. This research uses descriptive quantitative method of secondary data published by Bank Indonesia, ministry Finance and Jakarta Islamic Index. The result shows that the proportion of retail state sukuk against sharia state securities increases over time (over 50%) but the proportion of corporate sukuk numbers is still relatively small (below 25%).Â